The prevalence of urinary dysfunction in Hong Kong Chinese women - Brieger, G.M.; Yip, S.K.; Hin, L.Y.; Chung, T.K.H. (Obstetrics and gynecology (New York. 1953), 1996)
To determine the prevalence of urinary dysfunction in Hong Kong Chinese women. A telephone survey was conducted in the territory of Hong Kong. The subjects were a sample of women between the ages of 10 and 90 years. The main outcome determined was the prevalence of urinary dysfunction. We made 3248 calls, resulting in 819 evaluable responses. Stress incontinence was reported by 21% (174) of respondents, urgency or urge incontinence in 15% (120), urinary frequency in 19% (154), nocturia in 20% (166), bed-wetting in 4% (31), and voiding difficulties in 13% (109). Stress incontinence occurred as the only symptom in 7% (53), the combination of urgency and frequency in 1% (11), and mixed symptoms in 6% (52). Four percent required protective underwear or pads, with 2% wearing protective underwear continuously; 4% were incapacitated by their incontinence. Symptoms of urgency, urge incontinence, frequency, and nocturia increased with increasing age, but voiding difficulties and nocturnal enuresis were unrelated to age. Stress incontinence, urgency, urge incontinence, frequency, nocturia, and voiding difficulties increased with increasing parity to para 4. Urinary dysfunction and its patterns appear to be as common and incapacitating in Hong Kong Chinese as they are in other populations.